POLA KOMUNIKASI DEBT COLLECTOR DALAM PROSES PENAGIHAN KREDIT MIKRO KEPADA DEBITUR BANK MANDIRI (KCP MARPOYAN) PEKANBARU - Oktavinoarti, Della; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Bank Mandiri (Marpoyan Assistant Branch Office) on 2013 launched micro credit loan that is capital loan to help personal enterprises. The implementation of this capital loan isn’t run correcrly at all, it means there’s a problem. The problem is there is debitor who can’t pay their loan on the payday. So to solve the problem Bank Mandiri (Marpoyan Assistant Branch Office) Pekanbaru hired Debt Collector who particularly has aassignment to make sure debitor pay their loan on the payday. This research aims to find out about direct communication, verbal and non verbal communication, and also the form of debt collector’s communication patterns on the micro credit collection process to debitor of Bank Mandiri (Marpoyan Assistant Branch Office) Pekanbaru.This research using qualitative research method with descriptive approach and supported with Symbolic Interaction theory. The subject of this research was choosing by purposive sampling technique who consists of three debt collectors and two debitors. Data was collected through observation, interview and documentation, Data was analyst using Interactive model of Miles & Huberman. Meanwhile to achieve the validity of the data, researcher used the extension of participation, triangulation, and adequacy of reference.The results showed first, direct communication is debt collector on the interaction of micro credit collection process make a contact first with debitor directly by phone, and debt collector do the collection directly and has a face to face interaction. Second, verbal and non verbal communication is symbol that exchanged when debt collector and debitor have interact each other. The form of verbal communication is vocabulary, racing, intonation, timing, and the form of non verbal communication is fasial massages, gestural massages, and postural massages. Third, the form of communication pattern is one way interaction and direct interaction between debt collector and debitor on the process of micro credit collection to debitor appropriate to SOP that had assigned from the bank.Key Words: Communication Pattern, Debt Collector, Symbolic Interaction